Feeding wheat dried distillers' grains with solubles increases conjugated linoleic acid and unsaturated lipids in ovine milk without adversely affecting milk yield - Neofytou, Marina C.; Michael, Charoulla; Constantinou, Constantina; Sparaggis, Dionysis; Tzamaloukas, Ouranios (My University, 2021)
The aim of this research communication was to examine the effect of dietary supplementation with wheat-based dried distillers' grains with solubles (DDGS), a by-product of bioethanol production, on yield, composition, and fatty acid (FA) profile of ewe milk. Forty-five purebred mid-lactating Chios ewes (average milk yield 2.23 kg/d in 96 ± 5 d in lactation) were offered three iso-nitrogenous and iso-energetic diets (15 animals per diet) for a 10 d adaptation period followed by a 5-week recording and sampling period. The diets contained 0, 6, and 12% DDGS on DM basis for the DG0, DG6, and DG12 treatment, respectively, as a replacement of concentrate mix, whilst concentrate-to-forage ratio remained at 60:40 in all treatments. Individual milk yield, milk composition, and FA profile were recorded weekly and analyzed using a complete randomized design with repeated measurements. No significant differences were observed among groups concerning dry matter intake (overall mean of 2.59 kg/d), milk yield or 6% fat-corrected milk and milk protein percentage or protein yield. Milk fat percentage was decreased in the DG12 (4.76%) compared to DG0 (5.69%) without, however, significantly affecting the daily output of milk fat. The concentration of all major saturated FA between C4:0 to C16:0 was reduced, whereas long-chain (>16 carbons), mono-unsaturated and poly-unsaturated FAs were increased in the milk of DDGS groups. Among individual FA, increments of oleic acid and C18:1 trans-monoenes like C18:1 trans-10 and C18:1 trans-11 were demonstrated in DG12 group, whereas linoleic and conjugated linoleic acid (CLA cis-9, trans-11) were elevated in both DDGS groups compared to control. Changes in FA profile resulted in a decline in the atherogenic index of milk by 20% and 35% in DG6 and DG12 treatments, respectively, compared with control. In conclusion, feeding DDGS to dairy ewes increased the levels of unsaturated FA that are potentially beneficial for human health without adversely affecting milk, protein or fat yield.
Keywords: Bioethanol byproduct; Dairy ewe; Fatty acids; Rumenic acid